2010
DOI: 10.4103/0253-7184.68996
|View full text |Cite
|
Sign up to set email alerts
|

Management of cryptococcal meningitis in HIV-infected patients: Experience from western India

Abstract: Introduction:Cryptococcal meningitis is one of the acquired immunodeficiency syndrome defining infections with high mortality. Amphotericin B is the preferred drug for induction therapy. Despite advances in human immunodeficiency virus (HIV) treatment, Antiretroviral Treatment (ART) roll-out programs and availability of amphotericin B, cryptococcal meningitis remains an important cause of mortality in the African and other developing countries.Materials and Methods:We carried out a prospective observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
4
1
1
Order By: Relevance
“…Usual symptoms are headache and altered mental status, including personality changes, confusion, lethargy, obtundation, and coma. In our study, headache was the most common presenting complaint followed by nausea and [8,9] Contrary to our fi ndings, other studies had shown that HIV-infected patients had lesser CSF pleocytosis, lower CSF protein response and a higher rate of isolation from non-neural sites. One of our patients had a CSF WBC count of 3500 cells/cu mm, probably the highest reported value for CM.…”
Section: Discussioncontrasting
confidence: 95%
“…Usual symptoms are headache and altered mental status, including personality changes, confusion, lethargy, obtundation, and coma. In our study, headache was the most common presenting complaint followed by nausea and [8,9] Contrary to our fi ndings, other studies had shown that HIV-infected patients had lesser CSF pleocytosis, lower CSF protein response and a higher rate of isolation from non-neural sites. One of our patients had a CSF WBC count of 3500 cells/cu mm, probably the highest reported value for CM.…”
Section: Discussioncontrasting
confidence: 95%
“…Magnitude of CSF pleocytosis among patients without HIV infection was documented to be higher compared to patients with HIV infection. [ 15 ] Although we have a smaller HIV-negative group, similar findings were seen in our patients. An important observation in our patients was the lower degree of CSF pleocytosis and lower protein levels among the patients who succumbed probably reflecting the poor immunological status.…”
Section: Discussionsupporting
confidence: 88%
“…Deviations from the 14-day induction target were mainly a result of early mortality; clinicians’ decision to discontinue amphotericin B on account of improvement in the clinical status of the patient; and amphotericin B-related toxicity. Given the finding from a prospective study in India that even the standard 14-day amphotericin B monotherapy might be suboptimal for one third of patients, 26 clinicians’ decision to discontinue amphotericin B before 14 days on the premise of clinical improvement remains a concern. It is pertinent to mention that the South African National Department of Health (NDOH) conceded that completing the 14-day course of amphotericin B might not always be ‘feasible’ given the high demands for hospital beds and thus recommended that ‘… an earlier switch to oral fluconazole may be considered … [ by the clinician ] … if there has been a good clinical response’ 12 (p. 169).…”
Section: Discussionmentioning
confidence: 99%